2021
DOI: 10.1007/s11356-021-17774-y
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 induced panic on stock price and green finance markets: global economic recovery nexus from volatility dynamics

Abstract: This paper investigates the effect of different categories of essential COVID-19 data from 2020 to 2021 towards stock price dynamics and options markets. It applied the hypothetical method in which investors develop depression based on the understanding suggested by various green finance divisions. Furthermore, additional elements like panic, sentiment, and social networking sites may impact the attitude, size, and direction of green finance, subsequently impacting the security prices. We created new emotion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Here tourism can play a vital role to promote the rural economy. There is a positive association between rural development and tourism (Nguyen et al 2021b;Sadiq et al 2022b, c;Tan et al 2021). In this context, Nooripoor et al (2021) investigated whether tourism plays any role in rural development in Iran.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here tourism can play a vital role to promote the rural economy. There is a positive association between rural development and tourism (Nguyen et al 2021b;Sadiq et al 2022b, c;Tan et al 2021). In this context, Nooripoor et al (2021) investigated whether tourism plays any role in rural development in Iran.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed that RE, as well as agriculture, does impact environmental sustainability. Furthermore, Ikram et al, (2020) and Tan et al (2021), also explored this these variables associations. The data set of 14 years from 2000 to 2014 was tested.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fuel poverty scopes are limited because it considers only households that cannot keep their homes sufficiently heated as a result of costly plus aggregated fuel debts (Chien et al, 2021b;Xueying et al, 2021;Khanna et al, 2019). Contrarily, energy poverty is explained as the inadequate availability of power and clean cooking solutions to meet the basic energy needs of households (Tan et al, 2021;Acharya and Sadath, 2019). The study concerning energy poverty meaningfully examines the emerging nations with all manner of weather conditions (Sokołowski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%